2015
DOI: 10.1007/s10874-015-9304-6
|View full text |Cite
|
Sign up to set email alerts
|

Size-resolved characterisation of organic compounds in atmospheric aerosols collected at Welgegund, South Africa

Abstract: The organic fraction of atmospheric aerosols is 20 to 90 % of which only a small percentage has been chemically characterised. Two-dimensional gas chromatography with a time-of-flight mass spectrometer (GCxGC-TOFMS) is a powerful instrument used to chemically characterise organic compounds. Size-resolved characterisation and semi-quantification of ambient organic aerosol compounds were performed with a GCxGC-TOFMS for the first time in South Africa. Twenty-four-hour samples were collected for 1 year for three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 56 publications
(68 reference statements)
0
39
0
Order By: Relevance
“…A significant smaller number of compounds were pre-identified for the braai experiment, i.e. 50, compared to the 1056 organic compounds pre-identified by Booyens et al 15 This can be attributed to the difference in sampling periods, i.e. Booyens et al 15 collected 24-hour samples, while aerosol samples were only collected for~2 hours.…”
Section: Figurementioning
confidence: 82%
See 4 more Smart Citations
“…A significant smaller number of compounds were pre-identified for the braai experiment, i.e. 50, compared to the 1056 organic compounds pre-identified by Booyens et al 15 This can be attributed to the difference in sampling periods, i.e. Booyens et al 15 collected 24-hour samples, while aerosol samples were only collected for~2 hours.…”
Section: Figurementioning
confidence: 82%
“…50, compared to the 1056 organic compounds pre-identified by Booyens et al 15 This can be attributed to the difference in sampling periods, i.e. Booyens et al 15 collected 24-hour samples, while aerosol samples were only collected for~2 hours. In addition, the number of organic compounds presented by Booyens et al 15 was the combined number of organic compounds pre-identified for the entire one-year sampling campaign.…”
Section: Figurementioning
confidence: 92%
See 3 more Smart Citations